The Fecal Metagenomics of Malayan Pangolins Identifies an Extensive Adaptation to Myrmecophagy - Ma, Jing-E; Jiang, Hai-Ying; Li, Lin-Miao; Zhang, Xiu-Juan; Li, Guan-Yu; Li, Hui-Ming; Jin, Xue-Jun; Chen, Jin-Ping (Frontiers in Microbiology, 2018)
The intestinal flora of an animal, including the number and abundance of different microbial species and their functions, is closely related to animal diets and affects the physical condition of the host. The Malayan pangolin (Manis javanica) is an endangered animal that specializes in myrmecophagy. Analyzing the intestinal microbiome of the pangolin is imperative to protect this species. By sequencing the fecal metagenomes of four pangolins, we constructed a nonredundant catalog of 211,868 genes representing 1,811 metagenomic species. Based on the taxonomic annotation, for which Bacteroidetes (49.9%), Proteobacteria (32.2%) and Firmicutes (12.6%) were the three main phyla. The annotation of gene functions identified 5,044 genes from 88 different glycoside hydrolase (GH) families in the Carbohydrate-Active enZYmes (CAZy) database and 114 gene modules related to chitin-degrading enzymes, corresponding to the catalytic domains of GH18 family enzymes, containing chitinase genes of classes III and V in the data set. Fourteen gene modules corresponded to the catalytic domains of GH19 family enzymes, containing chitinase genes of classes I, II and IV. These genes were found in 37 species belonging to four phyla: Bacteroidetes, Cyanobacteria, Firmicutes, and Proteobacteria. Moreover, when the metabolic pathways of these genes were summarized, 41,711 genes were associated with 147 unique KEGG metabolic pathways, and these genes were assigned to two GO terms, metabolic process and catalytic activity. We also found several species that likely play roles in cellulose digestion and may be able to degrade chitin, including Enterobacter cloacae, Lactococcus lactis, Chitinimonas koreensis, and Chitinophaga pinensis. In addition, we revealed some intestinal microflora and genes related to pangolin diseases. Twenty-seven species were identified by STAMP analysis as differentially abundant in healthy and diseased animals: 20 species, including Cellulosilyticum lentocellum and Lactobacillus reuteri, were more abundant in healthy pangolins, while seven species, including Odoribacter splanchnicus, Marinilabilia salmonicolor, Xanthomonas citri, Xanthomonas vasicola, Oxalobacter formigenes, Prolixibacter bellariivorans, and Clostridium bolteae, were more abundant in diseased pangolins. These results will help to support pangolin conservation efforts.